Analysis of Barn Owl (Tyto alba) Diet at CSU Channel Islands and Their Potential to Control Rodents Within an Integrated Pest Management Program - Plascencia, Ivett; Sanchez, Erika (CSUCI Journal of Undergraduate Research, 2013)
We analyzed the barn owl (Tyto alba) diet on the campus of California State University Channel Islands (CSUCI) and explored the potential use of Tyto for the control of rodents. Owl-based Integrated Pest Management (IPM) is an alternative method to the wide-spread application of second-generation anticoagulant rodenticide (SGAR). Anticoagulants poisons work by reducing the ability of rodents to produce Vitamin K, a crucial enzyme that allows blood to clot and prevent the uncontrollable loss of blood. SAGAR have a high potential to kill non-target wildlife. We posit a more sustainable approach to rodent control at CSUCI would be to increase Tyto populations and therefore the corresponding predation pressure upon local rodents, ultimately reducing the numbers of potentially nuisance rodents and need for SGAR.